A sterility-associated long noncoding RNA involved in honey bee caste determination and adult queen and worker fertility - Carlos A. M. Cardoso-Junior; Gustavo J. Tibério; Marina C. Peruzzolo; Luiz C. Vieira; Denyse C. Lago; Alexandre R. Paschoal; Isobel Ronai; Benjamin P. Oldroyd; Klaus Hartfelder (Proceedings of the National Academy of Sciences, 2026)
Insect sociality is a major evolutionary transition based on the suppression of worker reproduction in favor of a queen’s reproductive monopoly. Although sophisticated insect societies have arisen independently on multiple occasions in the Hymenoptera (bees, ants, and wasps), how worker sterility evolved through natural selection is not fully understood. In honey bees ( Apis mellifera ), dietary cues (royal or worker jelly) and social chemical signals (e.g., queen pheromones) promote caste differentiation by modulating the levels of juvenile hormone (JH), the key physiological orchestrator of caste determination in larvae and the maintenance of caste identity in adults. However, the precise molecular effects of JH on the ovaries of larvae and adult bees remain open questions. Here, we describe lncov1 , a long noncoding RNA (lncRNA), whose expression correlates with sterility in the ovaries of larvae and adult honey bees. Mechanistically, the low JH levels in worker larvae promote high lncov1 expression in their ovaries, which subsequently show extensive programmed cell death. Moreover, lncov1 expression is tightly connected to a reduction in the reproductive capacity of adult queens and workers, as this lncRNA responds to key environmental cues that regulate fertility, including royal jelly and queen pheromone. The sequence conservation of the lncov1 gene across eusocial bees, especially the genus Apis , suggests the evolutionary stability of the JH/ lncov1 pathway. Therefore, by revealing how nutritional and social cues acting through JH and lncov1 shape queen and worker fertility in honey bees, these findings position lncRNAs as key components in the evolution of social complexity in insects.